Treatment of Acute Proximal Anterior Cruciate Ligament Tears—Part 1: Gap Formation and Stabilization Potential of Repair Techniques. Issue 1 (29th January 2020) - Bachmaier, Samuel; DiFelice, Gregory S.; Sonnery-Cottet, Bertrand; Douoguih, Wiemi A.; Smith, Patrick A.; Pace, Lee J.; Ritter, Daniel; Wijdicks, Coen A.
Background: Recently, there has been a resurgence of interest in primary repair of the anterior cruciate ligament (ACL), with fixation techniques evolving. However, to date, there have been no biomechanical studies comparing fixed to adjustable fixation repair techniques. Hypothesis: Adjustable ACL repair provides for improved stabilization compared with fixed techniques with respect to both gap formation and residual load-bearing capability. Study Design: Controlled laboratory study. Methods: A total of 4 different ACL repair techniques (n = 5 per group), including single– and double–cinch loop (CL) cortical button fixation as well as knotless single–suture anchor fixation, were tested using a porcine model. For adjustable single-CL loop fixation, additional preconditioning (10 cycles at 0.5 Hz) was performed. The force after fixation and the actuator displacement to achieve a time-zero preload of 10 N were measured for fixed techniques. Incrementally increasing cycling (1 mm/500 cycles) from 1 to 8 mm was performed for 4000 cycles at 0.75 Hz before pull to failure (50 mm/min). The final residual peak load and gap formation for each test block were analyzed as well as ultimate strength. Results: Knot tying of a single-CL over a button (mean ± SD, 0.66 ± 0.23 mm) and knotless anchor fixation (0.20 ± 0.12 mm) resulted in significant time-zero gaps ( P < .001) and significantly higher overall gap formation at reduced residual loading (analysis of covariance, P < .001) compared with both the double-CL loop and adjustable fixation techniques. The adjustable group showed the highest failure load and stiffness, at 305.7 N and 117.1 N/mm, respectively. The failure load of the knotted single-CL group was significantly reduced compared with all other groups ( P < .001). Conclusion: Adjustable single-CL cortical button fixation with intraoperative preconditioning optimized time-zero ACL tension and led to significantly improved stabilization and reduced gap formation, with the highest ultimate strength. Single-CL loop knot tying over the button and knotless anchor fixation resulted in time-zero gaps to achieve slight tension on the ACL and significantly higher gap formation at reduced load-bearing capability. Clinical Relevance: Although the clinical relevance of gap formation is uncertain, a biomechanical understanding of the stabilization potential of current ACL repair techniques is pertinent to the continued evolution of surgical approaches to enable better clinical outcomes.